Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1136/bcr-2019-229377
|View full text |Cite
|
Sign up to set email alerts
|

Adhesional small bowel obstruction related to stapling device from previous laparoscopic inguinal hernia repair

Abstract: Small bowel obstruction (SBO) is common surgical presenting problem, accounting for roughly 15 000 laparotomies per year in the UK. However, SBO post laparoscopic transabdominal preperitoneal (TAPP) inguinal hernia repair is uncommon with an estimated incidence of 0.2%–0.5%. The common causes for SBO post-TAPP include inadequate closure, port-site herniation and adhesions. Here, we present a case of adhesional SBO related to stapling device from previous laparoscopic inguinal hernia repair and review alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
6
0
3
Order By: Relevance
“…Nevertheless, some serious and potentially life-threatening complications may develop. SBO after TAPP is uncommon, with an estimated incidence of 0.2–0.5% [ 10 ]. It usually results from inadequate peritoneal closure, trocar site herniation, or adhesion [ 10 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, some serious and potentially life-threatening complications may develop. SBO after TAPP is uncommon, with an estimated incidence of 0.2–0.5% [ 10 ]. It usually results from inadequate peritoneal closure, trocar site herniation, or adhesion [ 10 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…SBO after TAPP is uncommon, with an estimated incidence of 0.2–0.5% [ 10 ]. It usually results from inadequate peritoneal closure, trocar site herniation, or adhesion [ 10 12 , 15 ]. PH caused by a disrupted peritoneum is extremely rare, but it will have serious consequences if not managed in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 There has also been one case report in the literature which describes an adhesional small bowel obstruction that was attributed to a tack that had been placed during a laparoscopic inguinal hernia repair. 6 In vitro animal studies in pigs and rats have demonstrated intra-abdominal adhesion formation following preperitoneal mesh placement of less than 1% at three months, significantly less than in IPOM techniques. [7][8][9] In our case report, there was a band adhesion at the preperitoneal mesh that had led to an internal hernia and caecal volvulus, however, whether the mesh had initiated the adhesion is uncertain.…”
Section: Discussionmentioning
confidence: 99%